Exergy, environmental and economic analysis of modified domestic solar water heater with glass-to-glass PV module. (1st March 2019) - Tewari, Kirti; Dev, Rahul
Abstract: The present communication highlights the annual performance of a novel modified domestic solar water heater (MDSWH) with glass-to-glass PV module. MDSWH is made of transparent and non-metallic materials to reduce the covered floor area in comparison to Flat plate collector (FPC) or Evacuated tubular collector (ETC). The modeling and simulation of MDSWH has been done using MATLAB R2014a and validated with experimental results of year 2017 for climatic condition of Allahabad, Uttar Pradesh, India. It is found that MDSWH maintains a higher temperature than conventional system (Flat plate collector based solar water heating system) throughout the day. Maximum water temperature in the collector tubes and storage tank of MDSWH has been found to be 75.7 °C (experimental 71.6 °C) at 16:00 h and 74.7 °C (experimental 70.5 °C) at 17:00 h theoretically in the month of June 2017. The annual heat gain, electrical energy gain, exergy, environmental and economic analysis of the system have been also performed. The overall thermal energy gain of 908.9 kWh and overall exergy gain of 109.56 kWh have been found for MDSWH. The characteristic equation for the system has been also established. Highlights: Thermal modeling of MDSWH with glass-to-glass PV module is presented. Thermal model is validated for the climatic condition of Allahabad. Annual performance, exergy and enviro-economic analysis of MDSWH are analyzed. A comparative study of MDSWH with the conventional systems is presented.